Biocompatible hyperbranched polyglycerol modified ß-cyclodextrin derivatives for docetaxel delivery - Xu, Z.; Zhang, Y.; Hu, Q.; Tang, Q.; Xu, J.; Wu, Jian-Ping; Kirk, T.; Ma, D.; Xue, W. (Elsevier, 2017)
© 2016 Elsevier B.V. The development of biocompatible vector for hydrophobic drug delivery remains a longstanding issue in cancer therapy. We design and synthesis a drug delivery system based on HPG modified ß-CD (ß-CD-HPG) by conjugating HPG branches onto ß-CD core and its structure was confirmed by NMR, FTIR, GPC and solubility. In vitro biocompatibility tests showed that HPG modification significantly improved red blood cells morphology alteration and hemolysis cause by ß-CD and ß-CD-HPG displayed cell safety apparently in a wide range of 0.01–1 mg/mL. An anti-cancer drug, docetaxel, was effectively encapsulated into ß-CD-HPG which wa s confirmed by DSC analysis. This copolymer could form nanoparticles with small size ( < 200 nm) and exhibited better DTX loading capacity and controlled release kinetics without initial burst release behavior compared with ß-CD. Furthermore, antitumor assay in vitro show that ß-CD-HPG/DTX effectively inhibited proliferation of human breast adenocarcinoma cells. Therefore, ß-CD-HPG/DTX exhibit great potential for cancer chemotherapy.